A pedra angular da teoria da libido de Freud: masoquismo e sadismo entre os anos de 1905 a 1919 - Rodrigues, Helena Zoneti (Universidade Federal de São Carlos, 2026)
This dissertation investigated Freud's conception of sadism and masochism between 1905 and 1919, first questioning whether such formations constitute particular pathological expressions or structural dimensions of human sexuality. The research examined the conceptual genealogy of the sadism-masochism pair, from its formulation in Richard von Krafft-Ebing's "Psychopathia Sexualis" (1886) to its reformulation by Freud in "Three Essays on the Theory of Sexuality" (1905). It demonstrated how Freud shifted sadism and masochism from the psychiatric field to conceive them as structural components of instinctual life. Perversion ceased to be understood solely as a pathological deviation and came to designate constitutive modalities of infantile sexuality and psychic organization. Sadism and masochism thus emerge as privileged expressions of the articulation between aggression, pleasure, pain, activity, and passivity, anticipating economic issues later developed in "Beyond the Pleasure Principle" (1920). The dissertation also analyzed Freud's additions to the "Three Essays" (1905) and the essays "Instincts and Their Vicissitudes" (1915) and "A Child Is Being Beaten" (1919). It was observed that, by incorporating concepts such as ambivalence, sadistic-anal organization, guilt, and the Oedipus complex, Freud broadens the metapsychological status of these formations. Masochism, therefore, ceases to be conceived merely as a derivation of sadism and comes to occupy a structural position in the constitution of subjectivity and moral consciousness. It can be concluded that sadism and masochism have become fundamental conceptual operators in Freudian drive theory, demonstrating that perversion is not external to normality, but a constitutive component of human experience.

Diese Dissertation untersuchte Freuds Konzeption von Sadismus und Masochismus zwischen 1905 und 1919 und ging zunächst der Frage nach, ob diese Phänomene spezifische pathologische Ausprägungen oder strukturelle Dimensionen der menschlichen Sexualität darstellen. Die Untersuchung analysierte die begriffliche Genealogie des Sadismus-Masochismus-Paares von seiner Formulierung in Richard von Krafft-Ebings „Psychopathia Sexualis“ (1886) bis zu seiner Neuformulierung durch Freud in „Drei Abhandlungen zur Sexualtheorie“ (1905). Sie zeigte, wie Freud Sadismus und Masochismus aus dem psychiatrischen Kontext herauslöste und sie als strukturelle Bestandteile des Trieblebens beschrieb. Perversion wurde nicht länger ausschließlich als pathologische Abweichung verstanden, sondern bezeichnete fortan konstitutive Modalitäten der infantilen Sexualität und der psychischen Organisation. Sadismus und Masochismus erweisen sich somit als privilegierte Ausdrucksformen des Zusammenspiels von Aggression, Lust, Schmerz, Aktivität und Passivität und nehmen damit ökonomische Fragestellungen vorweg, die später in „Jenseits des Lustprinzips“ (1920) behandelt werden. Die Dissertation analysiert zudem Freuds Ergänzungen zu den „Drei Abhandlungen“ (1905) sowie die Essays „Die Triebe und ihre Wandlungen“ (1915) und „Ein Kind wird geschlagen“ (1919). Es wurde festgestellt, dass Freud durch die Einbeziehung von Konzepten wie Ambivalenz, sadistisch-analer Organisation, Schuld und dem Ödipuskomplex den metapsychologischen Status dieser Phänomene erweitert. Masochismus wird daher nicht länger lediglich als Ableitung des Sadismus verstanden, sondern nimmt eine strukturelle Stellung in der Konstitution von Subjektivität und moralischem Bewusstsein ein. Daraus lässt sich schließen, dass Sadismus und Masochismus zu fundamentalen begrifflichen Operatoren in der Freudschen Triebtheorie geworden sind, was beweist, dass Perversion nicht außerhalb der Normalität liegt, sondern ein konstitutiver Bestandteil der menschlichen Erfahrung ist.
The cornerstone of Freud's libido theory: masochism and sadism between the years 1905 and 1919
La pierre angulaire de la théorie de la libido de Freud : le masochisme et le sadisme entre les années 1905 et 1919
Keywords: Freud; Masoquismo; Sadismo; Sadism; Masochism; Sadismus; Masochismus; Masochisme; Sadisme; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; 4. Educação de Qualidade